1988
DOI: 10.1136/hrt.60.5.434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propranolol on the QT intervals of normal individuals during exercise: a new method for studying interventions.

Abstract: sumARY A new method was used to study the effect of a single dose of propranolol on the QT intervals during exercise in 11 normal volunteers. They exercised maximally on a bicycle ergometer and repeated the test after taking propranolol (40 mg) by mouth two hours before. Electrocardiograms were continuously recorded on magnetic tape and the cardiac cycle length (RR interval) and the QT interval were measured every five seconds by a computer aided method. The RR-QT data from each test during the exercise phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Studies evaluating the effect of exercise on the QT interval have uniformly demonstrated that it shortens (43,44,46). However, the imprecision of rate correction formulas, particularly in the more rapid heart rate range, has precluded a fundamental understanding of the autonomic effects of exercise (and recovery) on cardiac repolarization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies evaluating the effect of exercise on the QT interval have uniformly demonstrated that it shortens (43,44,46). However, the imprecision of rate correction formulas, particularly in the more rapid heart rate range, has precluded a fundamental understanding of the autonomic effects of exercise (and recovery) on cardiac repolarization.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that these differences are related to the different autonomic milieus present during exercise versus atrial pacing. For example, Sarma et al (46) plotted the QT-RR relationship for a subject during complete exercise tests-once with a 40-mg oral dose of propranolol administered 2 to 3 h before the test and once without drug. The QT-RR relationship appeared to be exponential.…”
Section: Discussionmentioning
confidence: 99%
“…One would predict that handgrip, which activates the sympathetic nervous system, would lead to QT interval shortening in normal subjects, and would have little or no effect on the QT interval in subjects with down-regulated β-receptors, such as those with heart failure [3,12,21,22]. The lack of effect of handgrip on the QTc interval in heart failure is therefore not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that a monoexponential formula best fit the QT-versus-RR relation in humans. 33,34 Thus, the use of Bazett's formula might have biased the analysis of Wang et al 3 The present study was designed to assess the rate and concentration dependence of QT prolongation with three different dosages of sotalol in normal volunteers. Two other objectives were to confirm that a monoexponential formula fits the QT-versus-RR relation better than Bazett's formula and to deter-.…”
mentioning
confidence: 99%